THE ROLE AND IMPORTANCE OF SCHOLARS' SCIENTIFIC HERITAGE IN IMPROVING THE EFFECTIVENESS OF EDUCATION - F.A. Rahimova (Next Scientists Conferences, 2025)
This article describes the possibilities of using historical materials in primary school lessons. Additionally, the types of historical materials and the features of their use are examined using classroom examples.